PENGARUH WORKING CAPITAL MANAGEMENT & POLICIES DAN FINANCIAL LEVERAGE TERHADAP PROFITABILITAS - Djingga, Sheren Virelia; Ekadjaja, Agustin (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to aims about the effects of working capital management and policies and financial leverage on profitability non-cylical consumer goods manufacturing companies listed on the Indonesia Stock Exchange in the period of 2019-2021. This research used 43 samples and 129 data from manufacturing companies selected by purposive sampling method with multiple regression analysis as its processing techniques. Data were input and calculated by Microsoft Excel program and processed by Eviews 12 program. The results of this study show that working capital management and policies has a significant negative effect on profitability and financial leverage has no effect on profitability.The implication of this research is the need to increase the attention for factors that improve performance, effectiveness, and efficiency related to policies, operating activities, and decisions in the future which can be a positive impact for company’s performance.